On the Role of Productivity and Factor Accumulation in Economic Development in Latin America and the Caribbean - Christian Daude; Eduardo Fernandez-Arias (Inter-American Development Bank (IDB), 2010)
This paper combines development and growth accounting exercises with economic theory to estimate the relative importance of total factor productivity and the accumulation of factors of production in the economic development performance of Latin America. The regions development performance is assessed by contrast with various alternative benchmarks, both advanced countries and peer countries in other regions. The paper finds that total factor productivity is the predominant factor: low productivity and slow productivity growth, as opposed to impediments to factor accumulation, are the key to understanding Latin Americas low income relative to developed economies and its stagnation relative to other developing countries. While policies easing factor accumulation would help somewhat in improving productivity, for the most part, closing the productivity gap requires productivity-specific policies.
Keywords: O11; O47; 330; Economic growth; Total factor productivity; Development